The impact of Lime Grade 1 lime on different crops in Rwanda - International Center for Tropical Agriculture (2024)
In Rwanda, AGRA is leading one partnership under AID-I GLR Project. AGRA partnered with MULIMECO, a Lime Grade 1 processing company, to streamline the use of Lime Grade 1 in Rwanda to fight against soil acidity, henceforth increase yield. MULIMECO engages Agrodealers to create awareness and enhance adoption of Lime Grade 1 by farmers